Determinan aktivitas fisik kurang pada usia 10-64 tahun: Analisis data SKI tahun 2023 - Noranti Siagian; Rd. Halim; Marta Butar Butar; Hendra Dhermawan Sitanggang (JOURNAL OF Qualitative Health Research & Case Studies Reports, 2026)
Background: Insufficient physical activity is a condition in which individuals do not meet recommended levels of physical activity, involving various body movements that require energy, influenced by sociodemographic factors, smoking behavior, and obesity, and contributing to an increased risk of noncommunicable diseases. Purpose: To determine the factors associated with the incidence of physical inactivity among those aged 10-64 years. Method: This study employed a cross-sectional design with an analytical approach and secondary data from the 2023 Indonesian Health Survey (SKI). Univariate, bivariate, and multivariate analyses were conducted. Results: Most respondents reported low physical activity, with characteristics predominantly being of productive age, female, having secondary education, working, living in rural areas, non-smoking, and non-obese. Bivariate analysis showed a significant association between age, gender, occupation, and smoking behavior with low physical activity, while education, residence, and central obesity were not associated. The final multivariate analysis showed that age was the dominant factor associated with low physical activity among residents aged 10–64 years in Jambi Province. Conclusion: There was a relationship between age, gender, occupation, and smoking behavior with the incidence of low physical activity. There was no association between education, residence, and obesity with low physical activity, with age being the most dominant factor.   Keywords: Insufficient Physical Activity; Obesity; Occupation; Sociodemographic Characteristics; Smoking Behavior.